Co-injection of basic fluxes or BF flue dust with PC into a BF charged with 100% pellets : effects on slag formation and coal combustion - Ökvist, Lena Sundqvist (Luleå tekniska universitet, 2004)
Based on 100% pellets operation at BF No. 3 at SSAB Tunnplåt in Luleå a new pellet with CaO/SiO2=1 was developed during early nineties. The pellet showed good results in metallurgical laboratory test but caused slag formation problems in the bosh. A high basicity slag was formed during interaction with basic fluxes and its melting point was increased when the slag was finally reduced. By injection of basic fluxes, the slag formation problems in the bosh can be avoided. Without a sinter plant, dusts have to be recycled in a cold bonded briquette. Injection of some of BF flue dust would improve the properties of the briquette and may be beneficial for the BF process. Based on top charging or tuyere-injection of basic fluxes and the injection of BF flue dust studies have been done. The studies carried out will clarify some phenomena of slag formation and the effect of co- injection on coal combustion in the blast furnace, including the effect of: 1) basic fluxes on slag formation in the blast furnace, if they are top- charged; 2) basic fluxes on slag formation in the blast furnace, if they are tuyere injected; 3) chemical composition and metallurgical properties of pellet and fluxes on slag formation; 4) reduction conditions on (reduction temperature, reducing gas composition) on bosh slag formation; 5 co- injection of BOF slag or BF flue dust on coal combustion efficiency and BF performance. From the results, it can be concluded that the interaction between pellets and fluxes starts when softening and melting starts in the cohesive layer. By choosing fluxes of a high melting point the dissolution of them in the bosh slag can be delayed and the excessive basicity of the bosh slag can be limited. A basic flux with a low melting point will easily dissolve into the bosh slag causing its basicity to increase, which is beneficial to S refining when acid pellets are used. The formation of a bosh slag of excessive basicity (which causes BF operation disturbances, because its high melting point, increases further during ...